Role of Macrophages in Mobilization of Hematopoietic Progenitor Cells from Bone Marrow after Hemorrhagic Shock - Xiang, Meng (2012)
The release of hematopoietic progenitor cells (HPC) from bone marrow (BM) is under tight homeostatic control. Under stress conditions, HPC migrate from BM and egress into circulation to participate in immune response, wound repair, or tissue regeneration. Hemorrhagic shock with resuscitation (HS/R), resulting from severe trauma and major surgery, promotes HPC mobilization from BM, which in turn affects post-HS immune responses. In this study, we investigated the mechanism of HS/R regulation of HPC mobilization from BM. Using a mouse HS/R model we demonstrate that the endogenous alarmin molecule high-mobility group box 1 (HMGB1) mediates HS/R-induced G-CSF secretion from macrophages (Mφ) in a RAGE signaling-dependent manner. Secreted G-CSF, in turn, induces HPC egress from BM. We also show that activation of β-adrenergic receptors on Mφ by catecholamine mediates the HS/R-induced release of HMGB1. These data indicate that HS/R, a global ischemia/reperfusion stimulus, regulates HPC mobilization through a series of interacting pathways that include neuro-endocrine and innate immune systems, in which Mφ play a central role.